Erosive processes due to physical-biological interactions based in a cellular automata model (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Bahía Blanca Estuary (38° 50' S, 62° 30' W) presents salt marshes where interactions between the local main plant and the dominant crab generate some very characteristics salt pans. These pans alter the normal water circulation and condition its trajectory generating an erosive process. The removed sediment is then exported to the main estuary through the creeks that evolve from those biological-physical interactions. To study it, a conceptual model is proposed, based on the laws deduced from observation of these phenomena in the field, and then verified with measurable data within macroscale time units.The objective of this article is to model how the interaction between the crab C. granulata and the plant S. perennis modifies the landscape of the salt marsh and influences the loss of sediment with a Cellular Automata Model. Originally developed to study the effect of the interaction plant - crab in the formation of tidal creeks, the model copies the basic laws that dominate the problem based on purely biological factors. Finally, the volume of sediment that is removed and how it varies in time are evaluated. The model results a very good tool to integrate a large quantity of data collected recently and to be able to extract conclusions on processes that have a very slow dynamics. Additionally, it could reproduce faithfully the salt marsh landscape product of the plants - crab interaction.